2008
DOI: 10.1038/bjp.2008.158
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid receptor‐1 antagonist rimonabant inhibits platelet activation and reduces pro‐inflammatory chemokines and leukocytes in Zucker rats

Abstract: Background and purpose: We investigated the effect of rimonabant on inflammation and enhanced platelet reactivity in type 2 diabetic Zucker rats, an experimental model of impaired glucose tolerance and the metabolic syndrome. Experimental approach: Rimonabant (10 mg kg À1 by gavage) was fed for 2 weeks to 3-month-old male obese Zucker rats as an impaired glucose tolerance model and for 10 weeks to 6-month-old male obese Zucker rats as a model of the metabolic syndrome. RANTES (Regulated upon Activation, Normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…It has been reported that rimonabant reduced plasma levels of the pro-inflammatory cytokines monocyte chemoattractant protein-1 (MCP-1) and interleukin-12 (IL-12) in LDLR-/-mice fed a Western-type diet [13] . Positive modulation of circulating neutrophil and monocyte numbers, reduced platelet activation and lower levels of MCP-1 and regulated upon activation, normal T cell expressed and secreted (RANTES) by rimonabant in type 2 diabetic Zucker rats have also been reported [14] . we demonstrated that TNF-α-induced IL-6 production, IKKα/ β phosphorylation and IκB-α degradation were significantly attenuated by rimonabant in HUVEC.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that rimonabant reduced plasma levels of the pro-inflammatory cytokines monocyte chemoattractant protein-1 (MCP-1) and interleukin-12 (IL-12) in LDLR-/-mice fed a Western-type diet [13] . Positive modulation of circulating neutrophil and monocyte numbers, reduced platelet activation and lower levels of MCP-1 and regulated upon activation, normal T cell expressed and secreted (RANTES) by rimonabant in type 2 diabetic Zucker rats have also been reported [14] . we demonstrated that TNF-α-induced IL-6 production, IKKα/ β phosphorylation and IκB-α degradation were significantly attenuated by rimonabant in HUVEC.…”
Section: Discussionmentioning
confidence: 92%
“…Since ROS participate in cell signaling process and their regulation, 2-AG could potentiate its platelet aggregating power increasing ROS formation. Recently it has been demonstrated that antagonism of CB1 receptor depresses platelet activation in a mouse model of type 2 diabetes mellitus and reduces cardiovascular risk by lessening proinflammatory and proatherosclerotic cascades [Schäfer et al, 2008]. Treatment with rimonabant reduced fibrinogen binding, reduced thrombin-induced platelet aggregation and decreasing ADP-stimulated expression of pselectin, a platelet activation marker.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of rimonabant used in this work was similar to that used for other animal experiments 12,30) , and to the concentration approved for use as an antiobe- …”
Section: Discussionmentioning
confidence: 99%
“…was administered. Rimonabant and LPS concentrations were based on published findings 11,12) . Intestinal tension and blood pressure were measured from 30 min before administration of LPS to 5 h afterward, with readings taken every 30 min.…”
Section: Materials and Methods §Animal Preparationmentioning
confidence: 99%